1984
DOI: 10.1182/blood.v64.5.1042.bloodjournal6451042
|View full text |Cite
|
Sign up to set email alerts
|

Dense cells in sickle cell anemia: the effects of gene interaction

Abstract: In an attempt to uncover potential genetic sources of the clinical diversity of sickle cell anemia, we have characterized homozygous SS patients in the following ways: percentage of dense red blood cells (% F4) as determined from Percoll-Stractan continuous density gradients, alpha gene deletion, average percentage of hemoglobin F (% HbF), hemoglobin in g/dL, age, and sex. We find that alpha 4 individuals have a higher % F4 (mean 24% +/- 15%) than alpha 3 individuals (mean 12% +/- 8%) (P less than .005). Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 0 publications
1
26
0
2
Order By: Relevance
“…In exp. 58 a cell separation was also effected with a Percoll-Larex mixture (modified from a method used by Fabry et al [7]). This showed three layers of cells, not so well separated as in the Percoll alone.…”
Section: Methodsmentioning
confidence: 99%
“…In exp. 58 a cell separation was also effected with a Percoll-Larex mixture (modified from a method used by Fabry et al [7]). This showed three layers of cells, not so well separated as in the Percoll alone.…”
Section: Methodsmentioning
confidence: 99%
“…The higher Hb and hemotocrit level in S/S patients with concomitant a-thalassemia, and to a slightly lesser extent in heterozygotes, is probably the result of reduced homolysis [30] and a more homogeneous red cell population, as demonstrated in density studies [25,32,33]. Although patients with a-thalassemia and high Hb F had slightly larger red cells and a higher Hb level, the differences between low and high Hb F groups with a-thalassemia were not significant.…”
Section: -mentioning
confidence: 99%
“…However, most of the acute clinical manifestations of SCD are related to acute VOCs, which represents the first cause of hospitalization of a young-adult with SCD [1,6]. VOCs result from complex and still only partially known interactions between plasma factors and different cell types, including dense, dehydrated sickle cells and reticulocytes, endothelial cells, leukocytes and platelets [1, [10][11][12][13]. Pathophysiological studies have shown that the dense, dehydrated red cells play a central role in acute VOCs due to impaired flow as a consequence of either intravascular sickling or trapping of dense RBCs in post-capillary venules with associated microvascular obstruction and organ damage [1, 14,15].…”
Section: Introductionmentioning
confidence: 99%